ANALISIS PERENCANAAN PAJAK PPH PASAL 21 YANG DILAKUKAN KONSULTAN PAJAK TERHADAP KLIEN UNTUK MEMINIMALKAN BEBAN PAJAK (STUDI KASUS KONSULTAN PAJAK PT KADENA SINAR SOLUSI) - Aurellia Wijaya; Olivia Nainggolan (Jurnal Bina Akuntansi, 2022)
This research was done for the purpose of deciding the appropriate plan for corporate tax payer to reduce the amount of tax whom they see as a burden. The researcher uses the qualitative method with case studies and analytical description in researching the given analytical data. The collecting data phase was done by interviewing the related subjects, observation, and documentation to gain the correct information. Results of the research show the correct method that was used by consultant to helped clients in order to reduce burden was in fact gross method.